"Space Formed by Building" Part 1: Reading the Rotherham House through Its Materiality. Issue 3 (1st September 2020) - Gatley, Julia
ABSTRACT: Group Architects are New Zealand's best-known practitioners of regional modernism. They are associated with the search for New Zealandness in architecture, even as international interests are acknowledged. In 2003, Group member Bruce Rotherham (1926–2004) distanced himself from much of this commentary, emphasising his own early focus on "space formed by building", not New Zealandness. Of interest here is his privileging of building, that is, the assemblage and attributes of building materials. The article explores the materiality of Rotherham's best-known New Zealand building, the Rotherham House in Stanley Bay, Auckland (1951). It interrogates each of the four main materials used in the house: wood, stone, brick and glass. It asks, what is the history of each material, and what does the way it was used reveal about Rotherham's interests and influences? The article suggests that for Rotherham, Auckland's nineteenth-century Gothic Revival timber churches were a likely New Zealand source of influence. It then goes further than previous scholarship on the Group by suggesting specific overseas buildings that Rotherham is likely to have known and that anticipate the material palette of the Rotherham House. Reference to the 1930s and 40s work of Frank Lloyd Wright, Le Corbusier and Alvar Aalto is recurrent.